Nonstandard Work Schedules and Private Safety Nets Among Working Mothers. Issue 3 (19th September 2016) - Su, Jessica Houston; Dunifon, Rachel
Abstract : Although the implications of nonstandard work schedules (work outside of the typical 9 – 5, Monday – Friday schedule) for individuals and families are increasingly well understood, it is unclear how such schedules are associated with perceived social support for working mothers. Using data from the Fragile Families and Child Wellbeing Study and a variety of methodological approaches, we found mixed evidence for this relationship. Results from ordinary least squares and propensity‐weighted models suggest that working a nonstandard schedule is associated with weaker perceived support, particularly among those who are Black and less educated, and those who exclusively work such a schedule. Conversely, results from fixed‐effects models suggest that changing from a standard to a nonstandard schedule is associated with modest increases in perceived social support. These results add nuance to our understanding of the implications of nonstandard work schedules for families.